The child dental care reform in Israel – service uptake from 2011 to 2022 - Hagit Domb Herman; Hazav Dadosh; Dan Dekel; David Yellon; Shlomo Paul Zusman; Lena Natapov (Israel Journal of Health Policy Research, 2024)
Abstract Background The 2010 Child Dental Care Reform of the National Health Insurance Law marked a turning point in the Israeli oral healthcare system by establishing Universal Health Coverage of dental care for children. Initially, the reform included children up to age 8 and gradually expanded to age 18 in 2019. The basket of services includes preventive and restorative treatments provided by the four Health Maintenance Organizations (HMO). The aim of this study was to examine the uptake of child dental services during the first decade of the reform. Methods A retrospective analysis was conducted to determine the treatment uptake, type and amount of the services delivered based on annual service utilization reports submitted by the HMOs to the Ministry of Health in the years 2011–2022. Results The number of insured children increased from 1,546,857 in 2011 to 3,178,238 in 2022. The uptake of dental services gradually increased during the study period with a slight decrease in 2020. The percentage of children who used the services gradually increased from 8 to 33%, with the incremental inclusion of additional age groups. From 2012 onwards the most common treatments provided were preventive, however the single most common treatment was dental restoration. In 2022 35% of the population of Israel was under the age of 18. Out of these, about a third received dental treatment via the HMOs. This is a significant achievement, since before the reform all treatments were paid out-of-pocket. After a short period of increasing uptake, a stable service utilization pattern was evident that can indicate better public awareness and service acceptance. Conclusion Although this is a reasonable uptake, additional efforts are required to increase the number of children receiving dental care within the public insurance. Such an effort can be part of a multi-disciplinary approach, in which pediatricians and public health nurses can play a vital role in dental caries prevention, enhancement of awareness and service utilization.